Generalized Neutrosophic Sets and Its Application in KU-Algebras University of New Mexico - Ramesh Kumar D; Vasu M (Neutrosophic Sets and Systems)
The KU-algebras are given a GNeuS. In KU-algebras, the notions of GNeuSubAlg’s and GNI’s are introduced, and related properties are explored. The GNeuSubAlg/GNI is studied. There is a discussion of the relationship between GNeuSubAlg and GNI. Conditions for a GNeuSubAlg to be a GNI are given in a KU-algebra. There are also conditions for a GNeuS to be a GNI. We investigate the homomorphic image and preimage of the GNI.